System Biology Approach for Cardiovascular Medicine - Mariano, Cibelle (2018)
Objectives: This research project proposes the study of associaFons and/or interacFons between geneFc, nongeneFc and environmental factors and its effects on a very important dyslipidaemia marker, apolipoprotein B (apoB) levels, by modelling geneFc predisposiFon, biological and environmental components (such as lifestyle and behavioral variables) with apoB serum levels. It is also proposed the characterisaFon of the lipid and geneFc cardiovascular risk profiles of the Portuguese populaFon, as well as the correlaFon between dyslipidaemia and other cardiovascular risks and biochemical markers.